Analisis Disiplin Kerja Karyawan Pada Umkm Banana Cauji (Ciparay) - Supriani, Aprila; Maryono, Dicky (STIM-LPI Makassar, 2024)
This study aims to determine the application of work discipline in Banana Cauji micro, small and medium enterprises and to find out why Banana Cauji's performance is not optimal. The research method used is a qualitative approach, namely an approach that tends to lead to descriptive research methods and information or data presented in the form of statements. The data obtained in this study is primary data where the information obtained by the researcher comes from the source. The data collection techniques used are interviews, observation and documentation. Based on the research results obtained, it shows that there are still employees who have not implemented work discipline properly such as being late for work and absent. This conclusion confirms that there are no written rules and clear penalties and Banana Cauji's performance is still not optimal because it is caused by poor work discipline.